Growth of GRP in Chinese Provinces. A Test for Spatial Spillovers. - Krister Sandberg (European Regional Science Association (ERSA), 2004)
This paper examines the provincial pattern of growth in China during the period 1985–2000, testing the hypothesis that provinces with similar growth rates are more spatially clustered than would be expected by chance. The provincial economic growth is explained by the distribution of industrial enterprises, foreign direct investment, infrastructure, and governmental preferential policies. The neoclassical hypothesis of convergence is also tested. Indications of unconditional convergence does occur during the periods 1985–2000 and 1985–1990. In addition, conditional convergence is found during the sub-period 1990–1995. Evidence of spatial dependence between adjacent provinces has also been established, and in the econometric part, solved by a spatial lag, or alternatively a spatial error term, in the growth equation. Keywords: GRP-growth, Chinese provinces, Spatial dependence Classification [JEL]: O18, R11, R12
Keywords: O18; R11; R12; 330; GRP-growth; Chinese provinces; Spatial dependence